TMOD-18. THE PATIENT DERIVED XENOGRAFT NATIONAL RESOURCE: A COMPREHENSIVE COLLECTION OF HIGH-GRADE GLIOMA MODELS FOR PRE-CLINICAL AND TRANSLATIONAL STUDIES. (5th November 2018) - Vaubel, Rachael; Tian, Shulan; Remonde, Dioval; Schroeder, Mark; Kollmeyer, Thomas; Peng, Sen; Mladek, Ann; Carlson, Brett; Ma, Daniel; Kitange, Gaspar; Evers, Lisa; Decker, Paul; et al.
Abstract: Patient derived xenograft (PDX) models have shown great utility for pre-clinical and translational studies for a range of malignancies. We have established a comprehensive, publically available collection of 95 high-grade glioma flank PDX models. Viable PDX were derived from Glioblastoma, IDH-wildtype (n=91), Glioblastoma, IDH-mutant (n=2), Diffuse Midline Glioma, H3 K27M-mutant (n=1), and Anaplastic Oligodendroglioma (n=1) and include both primary (n=60) and recurrent (n=35) tumors. Comprehensive molecular characterization of PDX is ongoing and, to date, has included whole exome sequencing (WES, n=82), RNA-sequencing (n=40), and genome-wide methylation profiling (n=78) that included MGMT promoter, with data available in cBioPortal. PDX reflected the genetic characteristics of glioblastoma, with the majority harboring TERT promoter mutations, chromosomal gain +7, loss -10 and homozygous deletion of CKDN2A/B . EGFR alterations were frequent (~40%) and included amplification, point mutation, EGFRvIII, and other splice variants. Other common alterations, including amplifications of MET, CDK4, CDK6, MDM2, MDM4 and mutation of TP53, PTEN, NF1, RB1, PIK3CA, PIK3R1 were present at similar frequencies reported by TCGA, with the exception of PDGFRA alterations that were underrepresented in PDX. RNA-sequencing showed representation of each of the glioblastoma gene expression subtypes. To assess preservation of genetic features during xeongrafting, we performed WES on 20 matched patient tumors. The vast majority of genetic driver alterations were shared between patient and PDX, including EGFR, EGFRvIII, CDK4, MDM2, and MET amplifications. In 3 PDX, subclonal selection events were observed, including amplifications of MYCN, CDK6 and an EGFR splice variant, as well as selection against PDGFRA amplification. Overall, our large panel of PDX models reflects the genetic heterogeneity of glioblastoma and largely preserves the genetic features of the primary patient tumors. The PDX National Resource is a powerful tool for neuro-oncology research, with all PDX models and genomic data openly available (http://www.mayo.edu/research/labs/translational-neuro-oncology/mayo-clinic-brain-tumor-patient-derived-xenograft-national-resource ).